Coupling use of stable isotopes and functional genes as indicators for the impacts of artificial restoration on the carbon storage of a coastal wetland invaded by Spartina alterniflora, southeastern China - Chu, Tianshu; Li, Danyang; Shih, Yi-Jia; Guo, Yuqing; Liu, Kai; Ji, Fenfen; Li, Jun; Yin, Yuzhu; Chen, Ruohai (Frontiers in Marine Science, 2024)
Coastal wetlands are characterized by high production and thus play an important role in global climate change. In past decades, the invasion of Spartina alterniflora has caused many problems of coastal wetlands in southeastern China, and the restoration of such areas was mainly conducted by replacing Spartina alterniflora with mangrove plants. This may impact the carbon storage dynamics in such areas. In this study, stable isotopes (δ13C and δ15N) and molecular analysis were used to reveal the impact of artificial restoration on the carbon storage of Quanzhou Bay Estuary Wetland Natural Reserve. The major results are as follows: (1) the change in dominant plants results in a changing major source of soil organic matter, from external sources to mangrove plants; (2) the decrease in soil organic matter following the removal of Spartina alterniflora may be primarily caused by the loss of external organic matter, while the production of mangroves may offset such loss and enhance the content and stability of carbon storage over the long term; (3) microbial CO2 assimilation may serve as an alternative source of bioavailable carbon and thus support the activity of benthic community. Our results revealed the long-term benefits of such restoration on the carbon storage function of wetlands invaded by Spartina alterniflora. Furthermore, the integrating of isotopic tracers and molecular technology may provide new insights in understanding the response of the carbon storage in coastal areas to human activity.